Bacteroides Fragilis Transplantation Reverses Reproductive Senescence by Transporting Extracellular Vesicles Through the Gut‐Ovary Axis - Yan Xiong; Xiaoxue Lu; Bohao Li; Shiyao Xu; Beibei Fu; Zhou Sha; Rong Tian; Rui Yao; Qian Li; Jingmin Yan; Dong Guo; Zixuan Cong; et al. (Advanced Science, 2025)
Abstract The diverse and dynamic population of microorganisms present in the gut microbiota may affect host health. There are evidences to support the role of gut microbiota as a key player in reproductive development. Unfortunately, the relationship between reproductive disorders caused by aging and gut microbiota remains largely unknown. Here, it is shown for the first time that gut microorganism Bacteroides fragilis (BF) transplantation ameliorates ovarian aging by transporting extracellular vesicles (EVs) through the gut‐ovary axis. Mechanistically, miR‐1246 is enriched in EVs derived from BF‐treated intestinal cells, and these miR‐1246‐enriched EVs are transferred to ovaries, thereby effectively improving reproductive senescence by reducing oxidative stress in the ovaries. Specifically, miR‐1246 reduces the ubiquitination of p62 and stabilizes the protein level of p62 by targeting E3 ligase SKP2. Then Keap1‐Nrf2 complex is dissociated and Keap1 is recruited to form the p62‐Keap1 complex. With the dissociation of Keap1‐Nrf2 complex, Nrf2 is released and activated, thus promoting the transcription of antioxidant enzymes and relieving reproductive senescence. Collectively, the data indicates that intestinal cell‐derived EVs serve as natural information carriers in the crosstalk between the gut and the ovary, and intestinal microorganism transplantation is a promising approach for the treatment of ovarian dysfunction diseases.